Retrospection of Historical Traces: A Hypersemiotic Study on the Use of KNIL Uniforms in Contemporary Social Discourse - Hagijanto, Andrian Dektisa (DeKaVe, 2024)
The formulation of the problem in this study is used to answer the question of how the uniforms of the Dutch colonial army during the Indonesian war of independence are used by young people today. Contemporary social activities carried out by individuals characterized as colonial soldiers produce signs that are used to re-examine the social stigma about KNIL soldiers. Why is hypersimiotics used in forming opinions that contrast with the mainstream views that have been passed down in Indonesia about the cruel and evil Dutch colonial soldiers towards the Indonesian people? The aim is to explain the contemporary social activities carried out by several young Indonesians who have a history of KNIL soldier ancestry. It explains contemporary social activities through social media posts by these young people in an effort to create retrospective attitudes towards the historical traces of the existence of KNIL soldiers in the Dutch East Indies. The result of this study is to explain the activities carried out by the research subjects as a construction of signs with concepts that refer to the blurring of boundaries between signs, symbols, and reality, where meanings can become ambiguous or have multiple layers of interpretation. The signs are the embodiment of what is understood as signs that go beyond classical semiotics and become a form of hypersimiotics. These new sign constructions produce an articulation that is interpreted as a form of resistance to prevailing conditions. The stigma inherited about the cruel and evil KNIL soldiers will be changed with a positive perspective. A retrospective expression of the KNIL soldiers in their existence during the Dutch colonial era.